Factors Related To Hypertension Management Efforts In Female Workers At Bringharjo Traditional Market Yogyakarta - Indah Wijayanti (Alma Ata University Press, 2020)
Background: Hypertension is a condition of blood pressure in blood vessels increases chronically. Yogyakarta has a population of high blood pressure or hypertension reaches until 7,464 people, stating that hypertension in population aged >15 years is more common in women (63.96%) than men (36.04%) (Year Health Profile 2014 Yogyakarta City).Objective: To determine the risk factors associated with hypertension management efforts in female workers at Bringharjo Traditional Market.Method: An observational analytic study with a cross sectional approach. The population of this study is all female workers at Bringharjo Market with quantities of 4,140 people. The sampling technique uses Simple Random Sampling technique that is 365 people. The data collection tool is a questionnaire. The data were analyzed using chi square test.Results: Factors related to hypertension management efforts included blood pressure level p = 0.049, age p = 0.000, education p = 0,000, family history p = 0,000, service access p = 0.167, insurance ownership p = 0.171, information sources p = 0.118 and knowledge p = 0.010. There is a relationship between blood pressure level, age, education, family history and knowledge with hypertension management efforts. While health services access, insurance ownership and information sources have no relationship with hypertension management efforts.Conclusions and suggestions: There is a relationship between blood pressure level, age, education, family history and knowledge with hypertension management at Bringharjo Traditional Market, but there is no relationship between health services access, insurance ownership, and information sources, with respondents of hypertension management at Bringharjo Traditional Market. The results of this study are expected to be used as additional references and for respondents who are not yet aware of hypertension management to carry out routine checks and take medication regularly.